Analisis Kapasitas Angkat Dan Gaya-Gaya Yang Bekerja Pada Lengan Tower Crane Jaso Tipe J240 - Dodi Abrar; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Tower Crane is a material transfer tool that is widely used in the construction of high rise buildings. The purpose of using this tower crane is to facilitate the transfer of building materials from one place to the desired place, and using tower cranes will also speed up the process of building a multi-storey building. The large number of building buildings in the midst of a crowd threatens the lives of people who are around the construction area. This is because the arm range of the tower crane that is installed reaches out of the construction area, which is certainly no safety limit. To determine the level of security of the tower crane when working on a predetermined load, analysis of tower crane components is carried out from the load capacity and manual loading analysis and using inventory software on the arm of the tower crane. Based on the result of manual loading analysis, the minimum safety factor value is 6.54 and using software inventory is 6.28.Keywords : Specifications, loading analysis, maximum voltage, yield stress, safety factor.